Development of Interactive Smart Poster Media for Sexual Education Introduction to Children Aged 5–6 Years - Syaharra, Salsya Iffana; Sari, Meliana; Ahmed, Shakib (CV Berkah Syahdin Trust, 2025)
Purpose – A lack of interactive and developmentally appropriate educational tools has limited young children's understanding of basic sexual education. This study aims to develop an interactive smart poster as a responsive educational medium tailored for children aged 5–6 years to introduce foundational concepts of sexual education in an engaging and age-appropriate manner. Method – This research employed a Research and Development (R&D) design using the 4D model (Define, Design, Develop, Disseminate) by Thiagarajan, focusing on the development phase. Data were gathered through expert validation and practitioner assessments using standardized instruments to evaluate media validity and practicality. Validity assessments included aspects of visual design, language clarity, and media functionality. Practicality was measured based on the content’s relevance and its applicability in early childhood classroom settings. The instruments were reviewed by two content experts and two early childhood educators. Findings – The interactive smart poster achieved a validity score of 90.59%, indicating a high level of validity, and a practicality score of 90.71%, denoting high practicality. These results support the media’s suitability and potential effectiveness in introducing basic sexual education concepts to young learners. Research implications/limitations – The study is limited to the developmental stage and initial feasibility testing. Future studies should explore the long-term impact, scalability, and integration of the smart poster into diverse educational contexts. Originality/value – This study offers an innovative approach by integrating responsive visual media into early childhood sexual education. The use of smart posters represents a novel contribution to pedagogical tools aimed at fostering early awareness in a safe, engaging, and developmentally appropriate manner.